The Effect of Birth Ball Exercises during Pregnancy on Mode of Delivery in Primiparous Women - Kobra Mirzakhani; Zahra Hejazinia; Nahid Golmakani; Mohammad Ali Sardar; Mohammad Taghi Shakeri (Mashhad University of Medical Sciences, 2015)
Background & aim:  Considering the fact that cesarean section (c-section) poses greater risks of maternal and neonatal complications, compared to vaginal delivery, scholars seek different strategies to decrease the prevalence of this surgical procedure. Birth ball exercises during pregnancy are among the proposed strategies. Thus, this study aimed to determine the effect of using birth ball during pregnancy on mode of delivery in primiparous women. Methods:This clinical trial was conducted on 54 women, referring to the maternity ward of Omolbanin Hospital. Subjects were randomly assigned to intervention and control groups. The intervention group performed birth ball exercises for 4-6 weeks; on the other hand, the control group only received routine care. Data were collected using questionnaires, forms of examination and observation, and checklists for recording exercise movements on a weekly basis. Chi-square, Fisher's exact test, and Mann-Whitney U test were performed, using SPSS version 16. Results: Rates of vaginal delivery and c-section in the intervention group were 92.6% and 7.4%, respectively, while the corresponding values in the control group were 66.7% and 33.3%, respectively. Chi-square showed a significant difference between the two groups in terms of mode of delivery (P=0.018). Conclusion: Considering the significance of promoting vaginal delivery among women, performing birth ball exercises is recommended as a useful, non-pharmacological, and inexpensive strategy for reducing c-section rate.